Behavior of UHPC structural members subjected to pure torsion - Ismail, Mohammed (Kassel University Press, 2015)
"Ultra High Performance Concrete (UHPC) is characterized by a very high compressive strength which may reach more than 200 MPa. The behavior of this material under tension and compression actions has been established to be very brittle in nature. Discontinuous fibers (normally steel fibers) are usually added to the UHPC mix to introduce ductility. In order to investigate the beneficial effects of using fiber reinforced UHPC in structural members subjected to torsion, a series of experimental tests on 17 UHPC beams subjected to pure torsion were carried out. The test beams consisted of plain UHPC beams, UHPC beams reinforced with steel fibers only, UHPC reinforced with steel fibers and different combinations of traditional longitudinal and transverse reinforcement. The plain UHPC beams showed very brittle behavior, whereas the UHPC beams with steel fibers only showed a post cracking ductile behavior. The addition of little steel fiber volume (e.g.
Keywords: Torsion (Mécanique); Torsion; torsional stress; Electronic books